82.2k views
5 votes
F(n) = n^3– 2n
g(n)= 2n + 2
Find (f •g)(n)

2 Answers

3 votes

Answer:

2jj2j wnqj qkwk abaia aow w wka a9w wjw a8uaaia sks sis s8siwobsisi shkahza a

Explanation:

bs ak la ya s dyua youa au ab fusn aigska

User Satan Pandeya
by
5.7k points
4 votes

Answer:


\boxed{(f~.~g)(x) = 2n^4 + 2n^3 - 4n^2 -4n}

.

Explanation:

We know that


f(n) = n^3 - 2n


g(n) = 2n + 2

.

So


(f~.~g)(x) = f(n)~.~g(n)


(f~.~g)(x) = (n^3-2n)(2n + 2)


(f~.~g)(x) = n^3(2n + 2) - 2n(2n + 2)


(f~.~g)(x) = 2n^4 + 2n^3 - 4n^2 -4n

User Chen Lim
by
5.6k points